2023
DOI: 10.3390/brainsci13091258
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Flavonoids in Brain Disorders

Syed Hasan,
Nabeel Khatri,
Zainab N. Rahman
et al.

Abstract: Flavonoids are a large subgroup of polyphenols known to be sourced from over 6000 natural products, including fruits, vegetables, bark, and herbs. Due to their antioxidant properties, flavonoids have been implicated as a therapy source for many diseases and conditions, including inflammation, vasculitis, venous insufficiency, and hemorrhoids. Currently, some flavonoids are being researched for their antioxidant ability concerning neuroprotection. These flavonoids can penetrate the blood–brain barrier and, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…et al have shown that the tissue of ulcerative colitis exhibits strong mRNA expression for chemokines, as observed with MIP-1α and RANTES [38]. Numerous studies have shown that flavonoids, including flavanones, possess a broad range of biological activities including anti-inflammatory, antioxidant, anticancer, neuroprotective, and anti-atherosclerotic properties [39][40][41][42][43]. Natural or synthetic compounds show an inhibitory effect on MCP-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…et al have shown that the tissue of ulcerative colitis exhibits strong mRNA expression for chemokines, as observed with MIP-1α and RANTES [38]. Numerous studies have shown that flavonoids, including flavanones, possess a broad range of biological activities including anti-inflammatory, antioxidant, anticancer, neuroprotective, and anti-atherosclerotic properties [39][40][41][42][43]. Natural or synthetic compounds show an inhibitory effect on MCP-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive consumption of flavonoids leading to adverse effects often seems to be related to the overuse of supplements without consulting a doctor or knowing the proper dosage. This is especially a risk for people taking other medications because flavonoids may interact with them [ 133 ]. These seem to be extreme cases out of ignorance because flavonoids offer cognitive health benefits in humans, as long-term consumption through food has been shown to reduce the risk of cognitive decline.…”
Section: General Characteristics and Targets Of Flavonoidsmentioning
confidence: 99%
“…Phytochemicals derived from medicinal plants offer various medicinal and health benefits to the brain because of their antiapoptotic, antioxidant, and anti-inflammatory properties [9,10], and are important sources of drugs for the treatment of brain disease. Gypenoside XVII (GP-17; molecular formula: C 48 H 82 O 18 ; molecular weight: 947.2 g/mol; Figure 1A) is a gypenoside monomer found in medicinal plants such as Gynostemma pentaphyllum or Panax notoginseng.…”
Section: Introductionmentioning
confidence: 99%